Construction of layered micro-/nano-structured MoNiCo-S cathode and broad bean shell derived carbon anode for hybrid supercapacitors - Hao, Chen; Tan, Jizheng; Lv, Zijun; Jiang, Mingjiang; Ni, Chenghao; Shen, Yuru; Wang, Xiaohong (Journal of colloid and interface science, 2025)
The network structure can accelerate charge migration, while sulfide nanoparticles were rich in electrochemical active sites, making MoNiCo-S layered micro-/nano-materials have excellent electrochemical performance. [Display omitted] •MoNiCo-S with layered structure is fabricated by in-situ growth, etching, and sulfidation.•The waste broad bean shell is utilised for preparation of biomass-derived carbon (KBBC).•Biomass derived carbon with rich pore structure is prepared by calcination and activation.•The assembled SNZCMO-150//KBBC supercapacitor showed superior energy density. Transition metal sulfides, despite their abundance of electrochemically active sites, often demonstrate inadequate rate performance and mechanical stability. The development of a multi-dimensional hierarchical architecture has proven to be an effective approach to address the limitations associated with sulfides. In the present study, MoNiCo-S nanorods featuring hierarchical micro-/nano-structures were successfully synthesized through a straightforward methodology that involved “in situ growth-etching-vulcanization”. The one-dimensional nanostructure CoMoO4 served as both the substrate and metal source for the in-situ growth of ZIF-67. Subsequently, Lewis acid was introduced to facilitate the formation of hydroxides, ultimately leading to the synthesis of sulfides via ion exchange with sulfur ions. Due to its rational design and element composition, MoNiCo-S exhibited excellent capacitance (3125.1 F/g at 1 A/g) and cycling stability (capacitance retention rate of 72.9 % over 5,000 cycles). In addition, the broad bean shell derived carbon (KBBC), prepared through a carbonization and activation process, demonstrated a specific capacitance of 295.0 F/g and a cyclic capacitance retention of 99.6 %. The assembled MoNiCo-S//KBBC asymmetric supercapacitor devices achieves a high energy density of 78.5 Wh kg−1 at a power density of 1004.3 W kg−1. After 10,000 cycles, the device exhibited a capacitance retention rate of 107.9 %, indicating excellent cycling stability. This research contributes significantly to the advancement of sulfide materials in the context of performance optimization design.